The Effect of Financial Literacy, Attitudes Towards Money, and Financial Pressure on the Financial Well-being of Non-Profit Organization Workers in Indonesia - Firda Inten Rasyidah; Zaenal Arifin (Jurnal Indonesia Sosial Sains, 2024)
This study explores the influence of financial literacy, attitudes towards money, and financial pressures on the financial well-being of non-profit workers in Indonesia, an issue that is relevant given the high social activity but lack of attention to the financial well-being of workers, especially with the majority of them being low-income. Using the purposive sampling method on 108 respondents from various regions in Indonesia, the study's findings showed that financial literacy had a significant positive influence on financial well-being. In contrast, attitudes towards money had no significant effect. On the other hand, financial stress significantly negatively influences the financial well-being of workers of nonprofit organizations. These results emphasize the importance of efforts to improve financial literacy and pay attention to financial pressures in improving the financial well-being of non-profit workers in Indonesia.